Building competitive firms : incentives and capabilities - Luthria, Manjula; Nabi, Ijaz. (Washington, DC : World Bank, 2002)
This text presents a framework that empasizes the economic and policy incentives needed to create firms and national economies. It also identifies and explains the key capabilities that firms must develop in-house in order to become more competitive.
Includes bibliographical references and index.
oif 31/07/14
Loan
Keywords: International trade; Competition; Organizational effectiveness; Competition, International; Technological innovations -- Management; Investments, Foreign; Industrial efficiency